Alkali metal doped ruthenium dioxide nanosheets with lattice distortion as highly active oxygen evolution electrocatalysts in acidic media. Issue 16 (5th April 2023) - Tang, Hai; Kong, Ming; Cao, Wenwen; Ma, Wenguang; Ding, Jianjun; Shi, Chuanxin; Yang, Xiaodong; Shen, Qi; Sun, Yiqiang
Abstract : Developing economic and acid-compatible oxygen evolution electrocatalysts is vital for their practical application in proton exchange membrane water electrolyzers, which has drawn worldwide attention. Abstract : Developing economic and acid-compatible oxygen evolution electrocatalysts is vital for their practical application in proton exchange membrane water electrolyzers, which has drawn worldwide attention. Herein, Li doped RuO2 NSs with abundant lattice distortions were successfully prepared and used as highly active and durable oxygen evolution electrocatalysts. In particular, Li doped RuO2 NS electrodes exhibit excellent oxygen evolution reaction (OER) activity under acidic conditions with a low overpotential of 169 mV at 10 mA cm −2, which is about a 20-fold enhancement in catalytic activity in comparison with pristine RuO2 . As evidenced by HRTEM and EDLC measurements, the enhancement is mainly due to the incorporation of extraneous Li atoms in RuO2 induced rich lattice distortions and increased active site exposure. This work may provide a simple avenue for the synthesis of efficient acidic OER catalysts.